Pengolahan Presensi Siswa pada Sistem Akademik SMK Alma Ata Majenang - Edy Sahputro, slamet Cahyo (Jurnal Teknologi dan Bisnis, 2021)
The use of computer technology in data processing is necessary for the purposes of the learning process and administration in schools. Especially during a pandemic, every activity begins to depend on computer and network technology, namely the online system. In mid-2021, the government has permitted face-to-face learning (PTM) activities in schools by implementing health protocols. The attendance process at school still uses the handwritten method so it takes a lot of time, while the learning time is quite short. In addition, manual attendance still has various weaknesses including data that is piled up and data that is prone to loss. Therefore, a web-based student attendance application was created by utilizing the QR-Code scan feature to mark student attendance. The web-based Student Presence application using the QR-Code was developed using the Rational Unified Process (RUP) methodology with analysis and design tools using UML, and using HTML and PHP to code it. This research resulted in a web-based and QR-Code student attendance application, where this attendance application can be utilized in managing student attendance in face-to-face learning at school. The benefits of the Web-Based and QR-Code Student Presence application are to reduce physical contact and gathering time in the classroom during a pandemic so that it can reduce the risk of transmission of the Covid-19 virus and assist the process of reporting student attendance for the assessment process.